If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -5) = 4(y + 2) Reorder the terms: 6(-5 + y) = 4(y + 2) (-5 * 6 + y * 6) = 4(y + 2) (-30 + 6y) = 4(y + 2) Reorder the terms: -30 + 6y = 4(2 + y) -30 + 6y = (2 * 4 + y * 4) -30 + 6y = (8 + 4y) Solving -30 + 6y = 8 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -30 + 6y + -4y = 8 + 4y + -4y Combine like terms: 6y + -4y = 2y -30 + 2y = 8 + 4y + -4y Combine like terms: 4y + -4y = 0 -30 + 2y = 8 + 0 -30 + 2y = 8 Add '30' to each side of the equation. -30 + 30 + 2y = 8 + 30 Combine like terms: -30 + 30 = 0 0 + 2y = 8 + 30 2y = 8 + 30 Combine like terms: 8 + 30 = 38 2y = 38 Divide each side by '2'. y = 19 Simplifying y = 19
| 5y=10x+2 | | x*2-8=8 | | 5n+4=2n+33 | | 3(a+7)=36 | | a^5+4=15 | | C/3C | | 4x-11=46 | | 3x+5=-8x-4 | | 4t-9=0 | | 7m+5=55 | | 1.74x+x=.1 | | 6h-3=15 | | 3g+6=15 | | x/3+x/12=15/4 | | 4/x=5/-6 | | 3n^2+6n-13=0 | | R=ir | | (2x-3)*(2x-3)=25 | | 6+6x=4x-10 | | Y=(x-2)(x+3) | | 4sint+3cost=0 | | 3x+30=2x-10 | | Y=(x+4)(x+1) | | Y=(x+4)(c+1) | | 12w=14 | | w/4=7.2 | | -7x+5=1-3x | | 23x+14-14=7x-2-14 | | 2y(8-2y)= | | Sinx+x*cosx-sinx=0 | | F(x)=2x^3-5x^2+4-1 | | 7(w+10)+6=12w-12 |